Analyzing the use of videoconference by and for older adults in nursing homes: an interdisciplinary approach to learn from the pandemic - Racin, Céline; Minjard, Raphaël; Humbert, Christophe; Braccini, Vivien; Capelli, Fabien; Sueur, Cédric; Lemaire, Célia (Frontiers in Psychology, 2023)
During the Covid-19 pandemic and the resulting visitation restrictions, digital tools were used in many nursing homes in France to allow the elderly and their relatives to maintain social contact via videoconferencing. This article adopts an interdisciplinary approach to analyze the processes that affect the use of digital technologies. Drawing on the concept of “mediation”, it seeks to shed light on how individuals embrace these tools in a relational situation. The interviews and observations undertaken among residents, their relatives, professionals, and the directors of seven nursing homes in 2021, make it possible to outline the different forms of practices and uses and to identify the factors leading to the variations observed. While the key objective of these technical and technological tools is to compensate – on a functional level – for the communication problems and the isolation of individuals in order to promote residents’ “quality of life” by maintaining “social contact”, our study reveals that these tools’ uses and practices largely differ. It also shows considerable inequalities in terms of residents’ acquisition of subjective feelings of ownership of the tools. These are never attributed to isolated physical, cognitive, psychic, and social difficulties. It seems important to analyze how the technological mediation exercised by these tools influences how individuals relate to themselves and others, and also to examine the meaning that elderly nursing home residents, who are aging and in situations of dependency, give to this mediation. It must be said that these relational situations can act as mediators only if the material and unconscious mechanisms brought together by the tool make it possible to develop an intermediate space capable of then opening up a transitional space for individuals, groups, and institutions. The configurations that reveal obstacles to this process question the representations of care and assistance that are renewed in the relationships between the elderly, their relatives and nursing home professionals. The risks associated with the failure to take into account residents’ requests and consent explain the importance of our discussion on how certain uses of digital technologies may renew the dilemma between concerns for protection and respect for autonomy.